Pembelajaran Transformatif Dalam Kalangan Wanita Dewasa Yang Menunaikan Haji Di Perak: [Transformative Learning Among Adult Women That Has Performed Hajj In Perak] (Sains Humanika, 2021)
Transformative learning is a process of engaging with an individual’s referral framework including perspectives of meaning, habit, mind and thinking. This study was conducted to study the transformational learning that takes place in adult women in performing the Hajj. This study is designed to identify triggers, factors and effects .The methodology of this study uses semi-structured interviews. A total of 5 informants consisting of adult women aged 45 to 65 were selected using the snowball method. The results show that different triggering events in each individual can change the perspective of informants to change.  Factors help inform informants to support and encourage them to continue to move in a positive direction. Suggestions to future researchers may extend the scope of Malaysia including Sabah and Sarawak, study gender differences and use data triangulation.
Keywords: Transformative learning, perspective changes, trigger event, adult women , critical reflection